Vacinação, produção do cuidado e qualificação profissional na atenção primária à saúde: conhecimentos, práticas e entraves - Freitas, Manuela Lima de (2023)
General Objective: To analyze the knowledge, practices, qualifications and obstacles that involve vaccination as a tool for the production of care in Primary Health Care in a municipality in the metropolitan region of Salvador-Bahia. Specific objectives: To analyze the intersection between vaccination and professional qualification of the Primary Care Health team from the perspective of Comprehensiveness in a municipality in the metropolitan region of Salvador-Bahia; Promote the qualification of workers who work in PHC in Family Health Teams (eSF) for safe guidance related to vaccination with collaborative and interprofessional practices. Methodology: Qualitative, exploratory and field study carried out in a municipality in the metropolitan area of Salvador-Ba, in two stages that concerns scientific research and a technical product related to the theme. The research was carried out with Primary Health Care workers and users with complete vaccination through semi-structured interviews and a field diary. The number of research participants was 14 workers and 06 users, and workers the course is proposed for all workers at this level of care. The interpretation of the data used the trajectory of dialectical hermeneutics, enabling the meeting of two theoretical perspectives that go beyond description and strengthen the subjectivity of the study participants and, based on the findings, planning a technical action connected with the research. Results: Therefore, the study demonstrated that there are weaknesses and barriers, since misinformation, the lack of space for speaking and listening between workers and users contribute to perpetuating fragmented, competitive, little collaborative care that compromises the production of care. Careful. The non-involvement of the team in the process of promotion and guidance regarding vaccination limits and fragments care, which is still based on isolated actions and not shared among the team, which makes longitudinality and coordination of care difficult. Regarding the proposed qualification, reflection is expected with the aim of improving the development of work, deconstructing competitive practices between professionals, in order to improve collaborative skills and give new meaning to the responsibility related to immunization. Conclusion: In this way, it is understood that vaccinating is an act of collective health and that to do so requires professionals with integration between teaching, service and community, in order to follow paths that promote practices in dialogue with multiple knowledge and that have a positive impact on daily life of teams with implications for interprofessional practice, One path to this condition is professional qualification of all Primary Health Care workers in this municipality.